2009
DOI: 10.1007/s00595-008-3775-x
|View full text |Cite
|
Sign up to set email alerts
|

Successful utilization of coronary covered stents to treat a common hepatic artery pseudoaneurysm secondary to pancreatic fistula after Whipple’s procedure: Report of a case

Abstract: A 73-year-old man underwent a pylorus-preserving Whipple's procedure for distal cholangiocarcinoma. His postoperative course was complicated by the formation of a pancreatic fistula, which was initially managed conservatively. On postoperative day (POD) 86, he lost 100 ml of blood from the site of the pancreatic fistula. Contrast-enhanced computed tomography (CT) showed a pseudoaneurysm, 12 mm in diameter, in the common hepatic artery. The diameter of the pseudoaneurysm increased to 15 mm on POD 89, so we impl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Stent-graft placement was considered as the first option unless the stent-graft approach to the bleeding point was technically difficult [13171820212223]. Nonetheless, in long-term follow-up, stent-graft is always accompanied by a potential risk of stent occlusion.…”
Section: Discussionmentioning
confidence: 99%
“…Stent-graft placement was considered as the first option unless the stent-graft approach to the bleeding point was technically difficult [13171820212223]. Nonetheless, in long-term follow-up, stent-graft is always accompanied by a potential risk of stent occlusion.…”
Section: Discussionmentioning
confidence: 99%
“…To date, no long-term data are available concerning the safety and patency of the covered stent for visceral pseudoaneurysms after pancreatic surgery. [20]…”
Section: Discussionmentioning
confidence: 99%
“…The TAE with coils has been proven by many authors to be an efficacious and minimally invasive treatment of HAPs. 22,23 The liver can considerably tolerate embolization of the main hepatic artery without major consequences, 11,12 because of portail vein supplies, collaterals such as the inferior phrenic artery, and many intrahepatic collaterals. However, some authors have reported liver abscess formation, liver infarction with or without hepatic failure, and a temporary increase in transaminases after embolization of PHA or CHA.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, endovascular treatment has become the first choice of HAPs. In a review of the literature, 2,4,5,[12][13][14][15][16][17] we found stent graft placement for HAPs was only the case report. Furthermore, the procedure-related complications and follow-up outcomes were not mentioned in many articles.…”
Section: Introductionmentioning
confidence: 93%